Mitochondrial genetic diversity and phylogenetic relationships of Echinococcus multilocularis in Europe. - Santoro, Azzurra; Santolamazza, Federica; Cacciò, Simone M; La Rosa, Giuseppe; Antolová, Daniela; Auer, Herbert; Bagrade, Guna; Bandelj, Petra; Basso, Walter; Beck, Relja; Citterio, Carlo V; Davidson, Rebecca K; et al. (International Journal for Parasitology, 2024)
The cestode Echinococcus multilocularis is the causative agent of alveolar echinococcosis, a fatal zoonotic parasitic disease of the northern hemisphere. Red foxes are the main reservoir hosts and, likely, the main drivers of the geographic spread of the disease in Europe. Knowledge of genetic relationships among E. multilocularis isolates at a European scale is key to understanding the dispersal characteristics of E. multilocularis. Hence, the present study aimed to describe the genetic diversity of E. multilocularis isolates obtained from different host species in 19 European countries. Based on the analysis of complete nucleotide sequences of the cob, atp6, nad2, nad1 and cox1 mitochondrial genes (4,968 bp), 43 haplotypes were inferred. Four haplotypes represented 62.56% of the examined isolates (142/227), and one of these four haplotypes was found in each country investigated, except Svalbard, Norway. While the haplotypes from Svalbard were markedly different from all the others, mainland Europe appeared to be dominated by two main clusters, represented by most western, central and eastern European countries, and the Baltic countries and northeastern Poland, respectively. Moreover, one Asian-like haplotype was identified in Latvia and northeastern Poland. To better elucidate the presence of Asian genetic variants of E. multilocularis in Europe, and to obtain a more comprehensive Europe-wide coverage, further studies, including samples from endemic regions not investigated in the present study, especially some eastern European countries, are needed. Further, the present work proposes historical causes that may have contributed to shaping the current genetic variability of E. multilocularis in Europe.